PELATIHAN APLIKASI GAMMA AI SEBAGAI ALAT BANTU KREATIF DALAM PEMBELAJARAN DAN PRESENTASI SISWA-SISWI SMKN 5 PEKANBARU PELATIHAN APLIKASI GAMMA AI SEBAGAI ALAT BANTU KREATIF DALAM PEMBELAJARAN DAN PRESENTASI SISWA-SISWI SMKN 5 PEKANBARU - Vebby, Vebby; Afriansyah; Turnandes, Yogo (J-COSCIS : Journal of Computer Science Community Service, 2025)
The rapid development of Artificial Intelligence (AI) has opened up significant opportunities in the field of education, particularly in enhancing creativity and learning efficiency. One relevant application of AI is the use of Gamma AI to support the creation of engaging and interactive learning documents and presentations. In response to this potential, a community service program was carried out to train students of SMKN 5 Pekanbaru in utilizing Gamma AI. The training aimed to equip participants with fundamental knowledge, practical skills, and improved digital literacy to face the challenges of the digital era. The results of the program indicated a significant increase in students’ understanding of AI concepts, their ability to use Gamma AI effectively, and their motivation to further develop their skills. This activity also produced tangible outputs in the form of media publication and submission to a community service journal.